The German National Program on Psoriasis Health Care 2005-2015: results and experiences - Augustin, Matthias; Enk, Alexander (Archives of dermatological research, 2016)
In 2005, the first national psoriasis survey in Germany revealed large deficits in health care particularly in patients with moderate to severe disease. The consecutive goal was to improve health care for psoriasis countrywide. For this, a large-scale national program was initiated starting with a comprehensive analysis of structures and processes of care for psoriasis. Patient burden, economic impact and barriers to care were systematically analyzed. In order to optimize routine care, a S3 guideline, a set of outcomes measures and treatment goals, were developed. Implementation was enforced by the German Psoriasis Networks (PsoNet) connecting the most dedicated dermatologists. The annual National Conference on Health Care in Psoriasis established in 2009 consented National Health Care Goals in Psoriasis 2010-2015 and defined a set of quality indicators, which are monitored on a regular basis. Currently 28 regional networks including more than 800 dermatologists are active. Between 2005 and 2014 7 out of 8 quality indicators have markedly improved, and regional disparities were resolved. e.g., mean PASI (Psoriasis Area Severity Index) dropped from 11.4 to 8.1 and DLQI (Dermatology Life Quality Index) from 8.6 to 5.9. A decade of experience indicates that a coordinated nationwide psoriasis program based on goal orientation can contribute to better quality of care and optimized outcomes.